DNA methylation profiling reveals novel biomarkers and important roles for DNA methyltransferases in prostate cancer - Kobayashi, Yuya; Absher, Devin M.; Gulzar, Zulfiqar G.; Young, Sarah R.; McKenney, Jesse K.; Peehl, Donna M.; Brooks, James D.; Myers, Richard M.; Sherlock, Gavin

(untitled) (Genome Research, 2011)
Candidate gene-based studies have identified a handful of aberrant CpG DNA methylation events in prostate cancer. However, DNA methylation profiles have not been compared on a large scale between prostate tumor and normal prostate, and the mechanisms behind these alterations are unknown. In this study, we quantitatively profiled 95 primary prostate tumors and 86 benign adjacent prostate tissue samples for their DNA methylation levels at 26,333 CpGs representing 14,104 gene promoters by using the Illumina HumanMethylation27 platform. A 2-class Significance Analysis of this data set revealed 5912 CpG sites with increased DNA methylation and 2151 CpG sites with decreased DNA methylation in tumors (FDR < 0.8%). Prediction Analysis of this data set identified 87 CpGs that are the most predictive diagnostic methylation biomarkers of prostate cancer. By integrating available clinical follow-up data, we also identified 69 prognostic DNA methylation alterations that correlate with biochemical recurrence of the tumor. To identify the mechanisms responsible for these genome-wide DNA methylation alterations, we measured the gene expression levels of several DNA methyltransferases (DNMTs) and their interacting proteins by TaqMan qPCR and observed increased expression of DNMT3A2, DNMT3B, and EZH2 in tumors. Subsequent transient transfection assays in cultured primary prostate cells revealed that DNMT3B1 and DNMT3B2 overexpression resulted in increased methylation of a substantial subset of CpG sites that showed tumor-specific increased methylation.